Prinsip Kehati-Hatian pada Lembaga Perbankan dalam Pemberian Kredit - Lukmanul Hakim; Travilta Oktaria (Universitas Bandar Lampung (UBL), 2018)
Banks are institutions that channel credit as much as possible and serves to increase the need for services for banking services to the community. Banking competition is increasingly stringent, banks are required to proactively provide credit products that can meet the needs of diverse communities with innovative product design, competitive, responsive to the needs of customers and profitable.To anticipate and review the competition between one bank with another bank, the funds collected must be planned properly and maximally so that it can be channeled to the community through a credit loan. In connection with the application of prudential banking principles or known as prudential banking. The problem of this research is how to apply prudential principles in lending to customers. The method used in this study is the normative juridical approach, the examination of the rules, norms, rules and further analysis of the data used is qualitative jurisdiction. Based on the results of the research shows that the application of prudential principles in the provision of credit to customers conducted by banking institutions to minimize the occurrence of bad loans. Implementation of several rules before giving credit to customers has been done, by implementing the basic principles of crediting and carrying out prudential principles such as Principle 5C which is character, capacity, capital, collateral, and condition of economy.